2019
DOI: 10.1371/journal.pone.0217333
|View full text |Cite|
|
Sign up to set email alerts
|

Potential user interest in new long-acting contraceptives: Results from a mixed methods study in Burkina Faso and Uganda

Abstract: Method-related concerns represent an important cause of contraceptive non-use and discontinuation. User preferences must be incorporated into the design of new contraceptive technologies to ensure product success and improve family planning outcomes. We assessed preferences among potential users in Burkina Faso and Uganda for six contraceptive methods currently under development or ready for introduction: a new copper intra-uterine device (IUD), a levonorgestrel intra-uterine system, a new single-rod implant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 12 publications
2
65
0
2
Order By: Relevance
“…Our nding that increased menstrual bleeding was associated with discontinuation aligns with a growing body of literature, highlighting the importance of contraceptive-induced bleeding changes (1,21). Excessive bleeding arose as a major barrier to contraceptive use in previous qualitative research in Uganda (18,37,38); that excessive bleeding was strongly associated with discontinuation, but not with switching, indicates that women who experience this side-effect may be reluctant to switch to new methods, instead preferring to discontinue use altogether. The experience of excessive bleeding may present practical challenges to menstrual hygiene management.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our nding that increased menstrual bleeding was associated with discontinuation aligns with a growing body of literature, highlighting the importance of contraceptive-induced bleeding changes (1,21). Excessive bleeding arose as a major barrier to contraceptive use in previous qualitative research in Uganda (18,37,38); that excessive bleeding was strongly associated with discontinuation, but not with switching, indicates that women who experience this side-effect may be reluctant to switch to new methods, instead preferring to discontinue use altogether. The experience of excessive bleeding may present practical challenges to menstrual hygiene management.…”
Section: Discussionsupporting
confidence: 79%
“…We did not nd signi cant effects with discontinuation or switching among women who reported less bleeding, although irregular bleeding was shown to reduce the risk of switching. Evidence from qualitative studies in Africa suggests that amenorrhea and irregular bleeding are often viewed negatively and associated with concerns about future fertility, particularly among nulliparous women (21), however recent qualitative evidence in Uganda found that the potential for lighter periods as a side-effect of contraception was viewed favorably by women (38). Of note, however, we did not distinguish between less bleeding and cessation of bleeding.…”
Section: Discussionmentioning
confidence: 58%
“…Excessive bleeding arose as a major barrier to contraceptive use in previous qualitative research in Uganda (22,35,36); that excessive bleeding was strongly associated with discontinuation, but not with switching, indicates that women who experience this side effect may be reluctant to switch to new methods, instead preferring to discontinue use altogether. The experience of excessive bleeding may be additionally problematic in environments like Uganda, where myths and misperceptions around the harmful impacts of contraception, including effects on future fertility and on overall health, are widespread (22,37,38).…”
Section: Discussionmentioning
confidence: 93%
“…This belief carries profound social consequences and, therefore, may greatly reduce motivation to use contraception (17,39) We did not nd signi cant effects with discontinuation or switching among women who reported less bleeding, although irregular bleeding was shown to reduce the risk of switching. Evidence from qualitative studies in Africa suggests that amenorrhea and irregular bleeding are often viewed negatively and associated with concerns about future fertility, particularly among nulliparous women (11), however recent qualitative evidence in Uganda found that the potential for lighter periods as a side effect of contraception was viewed favorably by women (36). Zimmerman and colleagues found that two-thirds of sexually active women in Uganda strongly agreed that not having a menstrual period as a result of contraceptive use was unhealthy, but agreement was not strongly associated with either discontinuation or switching (Under Review).…”
Section: Discussionmentioning
confidence: 99%
“…A longer-acting injectable could facilitate use, improve continuation, possibly increase effectiveness, and provide women with greater choice. Six months is a target duration from a safety perspective for a hormonal method that cannot be discontinued immediately in case of unwanted side effects or emerging medical contraindications and is preferred by both users and providers ( 5 ). While efforts are under way to develop novel sustained drug delivery technologies that hold promise for the development of a new 6-month injectable contraceptive product ( 6 , 7 ), the adaptation of existing methods for novel uses is an appealing, cost-efficient approach to expedite availability of new contraceptive options.…”
mentioning
confidence: 99%